Evaluation of anti-microbial potential of some medicinal plants - Mansoor Ahmad; Farah Saeed; Meh jabeen; Sikandar Khan Sherwani; Noor Jahan (International Journal of Phytomedicine, 2014)
The ethanolic extracts of the eight medicinal plants were tested to determine antibacterial activities against fourteen gram positive and twenty two gram negative bacteria. Five out of eight extracts revealed prominent antibacterial activity. Ampicillin was used as a standard for anti-bacterial activity. The significant zone of inhibition was exhibited by Digitalis purpurae (23±2) against Corynebacterium hofmanii. Sambucus nigra and Urtica urens exhibited minimum inhibitory concentration (12 mg/ml) against Staphylococcus epidermidis and Streptococcus fecalis. Saprophytes, dermatophytes and yeasts were used to screen antifungal activities of these selected medicinal plants. Griseofulvin was used as a standard anti-fungal drug. Four out of eight of the tested plant extracts had significant antifungal activity. Urtica uren produced the most significant zone of inhibition (32±1) against Rhizopus specie. Whereas the lowest minimum inhibitory concentration was exhibited by Urtica urens (20mg/ml) against Aspergillus flavus. The above results justify the use of medicinal plants and its extracts in the formulation of anti-microbial medicaments.